Frontiers in aging special issue: DNA repair and interventions in aging perspective on “loss of epigenetic information as a cause of mammalian aging” - Schaffer, Ethan D.; Beerman, Isabel; de Cabo, Rafael; Brosh, Robert M. (Frontiers in Aging, 2023)
The recently published article in Cell by the Sinclair lab and collaborators entitled "Loss of Epigenetic Information as a Cause of Mammalian Aging" [1] implicates heritable changes in gene expression as the basis for aging, a postulate consistent with the emerging information theory of aging. Sinclair's group and colleagues induced epigenetic changes, i.e., DNA and histone modifications, via double-strand breaks (DSBs) catalyzed by the I-Pol endonuclease at specific genomic loci. The genomic DNA breaks, introduced without inducing insertion or deletion mutations (indels) in a mouse model, were targeted to 19 non-coding regions and one region in ribosomal DNA (rDNA), the latter shown to not have a significant effect on the function or transcription of rDNA [1]. With that experimental model in place, the authors present experimental evidence supporting a model that epigenetic changes drive aging via this inducible DNA break mechanism. After demonstrating the phenotypic alterations of this accelerated aging, they attempt to reverse selective phenotypes by resetting the altered epigenetic landscape.Establishing a causal relationship between epigenetic changes and aging, and how this connection might be manipulated to overturn cellular features of aging, is provocative and merits further study.